Leakage of dissolved organic carbon (DOC) and photopigments from the diatom Skeletonema marinoi incubated in rotating pressure and control tanks - Stief, Peter (In: Stief, Peter; Schauberger, Clemens; Becker, Kevin W; Elvert, Marcus; Balmonte, John Paul; Franco-Cisterna, Belén; Middelboe, Mathias; Glud, Ronnie N (2023): Effects of increasing hydrostatic pressure on sinking diatom aggregates [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.960357, 2023)
The effect of increasing hydrostatic pressure on the microbial degradation, the organic matter composition, and the microbiome of 'marine snow' particles was studied in laboratory incubation experiments. Model aggregates were produced from the diatom Skeletonema marinoi and the natural microbial community of surface seawater collected in the Kattegat. The aggregates were incubated individually in rotating pressure and control tanks to keep them suspended during 20-day incubations in the dark and at 3°C. In the pressure tanks, hydrostatic pressure was increased at increments of 5 MPa per day to finally reach 100 MPa. This pressure scheme simulates the descent of diatom aggregates from the surface ocean down into a 10-km deep hadal trench. In the control tanks, pressure was always left at atmospheric level. The same overall experimental design was used to study the potential leakage of dissolved organic carbon (DOC) and photopigments from pure cultures of S. marinoi. DOC leakage was assessed from measuring concentrations of DOC in the seawater in which S. marinoi was suspended as well as DOC extracted from S. marinoi cells by freeze-thaw cycling. Potential photopigment leakage was assessed from measuring intracellular concentrations of the dominant pigments chlorophyll a and fucoxanthin after extraction with acetone:ethanol (50:50). Samples for DOC and photopigment measurements were retrieved every 4 days throughout the 20-day incubation experiment.
Keywords: biological carbon pump; Deep sea; Diatom; Hadal trench; hydrostatic pressure; Laboratory experiment; lipids; marine carbon cycle; marine snow; microbial community; Pigments; Respiration